2007
DOI: 10.1094/phyto-97-7-0813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microclimate on Leveillula taurica Powdery Mildew of Sweet Pepper

Abstract: Sweet pepper-Leveillula taurica microclimate relations were studied under controlled conditions and in commercial greenhouses. Conidial germination occurred at 10 to 37 degrees C and was optimal at 20 degrees C. Conidial viability declined as temperatures increased to 40 degrees C for 6 h. Leaf colonization was optimal at 15 to 25 degrees C. Severe leaf infections occurred at 15 to 20 degrees C and conidiation was suppressed at 20 to 25 degrees C. Highest germination rates were observed at 75 to 85% relative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
1
22
1
6
Order By: Relevance
“…Unlike earlier results (data not shown here, see Elad et al 2007), no cultivar effect was noticed, except for one evaluation of leaf coverage. Night-time temperature significantly affected the disease leaf coverage and shedding.…”
Section: Control Of Pepper Powdery Mildew By Bcas and Oilscontrasting
confidence: 95%
See 3 more Smart Citations
“…Unlike earlier results (data not shown here, see Elad et al 2007), no cultivar effect was noticed, except for one evaluation of leaf coverage. Night-time temperature significantly affected the disease leaf coverage and shedding.…”
Section: Control Of Pepper Powdery Mildew By Bcas and Oilscontrasting
confidence: 95%
“…Sweet pepper (Capsicum anuum) is an important crop in Israel (2240 ha in greenhouses and net houses) (Elad et al 2007). Powdery mildew, caused by Leveillula taurica is a major problem in this crop; it attacks pepper in all cropping regions; farmers treat plants by spraying intensively, sometimes with low control efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two azoxystrobin applications restricted the disease progress on field bindweed and pepper plants (Tables 2 and 3). In contrast, Elad et al (2007) reported that the current recommendation for powdery mildew control is frequent fungicide applications beginning early in the season. Concerning the disease severity in the prevent study, there were no significant differences between the weed-free control and field bindweed treatment.…”
Section: Resultsmentioning
confidence: 96%